Orthopedic Insole Design and Pressure Analyzes - Özkan, Salih; Altural, Hayriye; Kandemirli, Güzin Çakır; Kandemirli, Fatma (IEEE, 2018)
In this study, it was aimed to produce a low cost customized orthopedic insole and perform its pressure analyzes. In this analysis, it was used thin film pressure sensor and Arduino programming platform equipped with ATmega328 microcontroller. For the sensor layout, 5 zones were determined in the sole and the proportional values with the pressure were recorded and these values were used for the insole design. For the pressure analysis, 17 volunteers aged 19 to 34 years, with flatfoot and normal foot participated for the experiments. A center line was determined to provide a balanced distribution of the pressure in the sole and a mathematical model was created for this distribution. Through this model, the data obtained from the experiments was normalized and the appropriate height values were calculated for the insole zones. In addition to this study, the reduction degree of pressure applied to the sole of a 9 mm high foam material placed on the heel of the foot was measured.